Impact of posttraumatic growth on the quality of life in woman with breast cancer - Suharda Chabirah; Emmi Bujawati; Habibi Habibi; Azriful Azriful (Al-Sihah : The Public Health Science Journal, 2020)
Cancer is an abnormal cell condition that can grow faster than usual condition which makes it difficult to control. Posttraumatic Growth is a reactive psychopathological response to traumatic events. Someone who has been diagnosed with breast cancer will experience physical, psychological, and social change as well as difficulties in both sexual and daily activities. This situation is going to be affect the quality of life of patients. This study aims to look at the relationship of posttraumatic growth and the quality of life of breast cancer patients in Makassar general hospital (RSUD). This research was quantitative research with an observational analytic approach and cross-sectional study design. The research site was in RSUD Makassar. The sampling technique used was a total sampling technique in which 34 respondents were selected. The Chi-Square test results confirmed that there were significant influences of factors such as social relationship new opportunities internal strength spiritual development the expected life value and posttraumatic growth on the quality of life of patients with Ca. Mammae. Therefore, for further research in the similar scope, it is expected for future researchers to conduct research in diverse cultural settings or by adding other psychological perspectives to be discussed in the research.